High-open-circuit-voltage wide-band-gap perovskite solar cell and preparation method thereof

By adding betaine citrate to the assembly monolayer and precursor solution of perovskite solar cells, the problems of high defect state density and large open circuit voltage loss inside wide bandgap perovskite solar cells were solved, achieving higher Open circuit voltage and photoelectric conversion efficiency.

CN119342972APending Publication Date: 2025-01-21GUANGDONG BENSHU LIGHT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475111.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Wide-bandgap perovskite solar cells face problems such as high internal defect state density, easy phase separation in light-induced light, and large open-circuit voltage loss.

Method used

By adding citrate betaine to the assembled monolayer (SAM) and perovskite precursor solution, a perovskite solar cell with multifunctional passivation effect was prepared.

Benefits of technology

The realization of perovskite solar cells with higher open circuit voltage, better photoelectric conversion efficiency and stability has effectively promoted the commercialization process of perovskite solar energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119342972A_ABST
    Figure CN119342972A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-band-gap perovskite solar cell with high open-circuit voltage and a preparation method of the wide-band-gap perovskite solar cell. The broadband gap perovskite solar cell is composed of a transparent conductive substrate, a hole transport layer, an organic-inorganic hybrid metal halide perovskite light absorption layer, a surface defect passivation layer, a metal fluoride layer, an electron transport layer, a hole barrier layer and a metal electrode. Wherein citric acid betaine is added into the hole transport layer and the organic-inorganic hybrid metal halide perovskite light absorption layer. According to the invention, the wettability of the hole transport layer is improved, and the growth of perovskite crystal grains is facilitated; the defects of the perovskite thin film are passivated, and non-radiative recombination and open-circuit voltage loss are reduced; the open-circuit voltage and the filling are obviously improved, and finally higher photoelectric conversion efficiency is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a wide bandgap perovskite solar cell with high open circuit voltage and a preparation method thereof. Background Art

[0002] Solar energy is one of the most widespread and abundant renewable energy sources on earth, and photovoltaic technology has attracted much attention due to its cleanliness and efficiency. Perovskite solar cells, as a new type of thin-film solar cell, have developed rapidly, and the cell efficiency has exceeded 26%, showing good development prospects. Wide-bandgap perovskite solar cells with a bandgap width greater than 1.7eV can be stacked with silicon cells, copper indium gallium selenide cells and narrow-bandgap perovskite cells to prepare stacked cells, which is expected to break through the Shockley-Queisser efficiency limit and maximize the use of solar energy.

[0003] However, wide-bandgap perovskite solar cells often face problems such as high internal defect state density, easy photoinduced phase separation, and large open-circuit voltage loss. These challenges are mainly due to non-radiative recombination losses at the interface between the perovskite absorber layer and the hole transport layer or electron transport layer, and phase separation caused by the movement of halide ions at grain boundaries.

[0004] Therefore, it is urgent to introduce effective multifunctional additives to passivate the trap states on the surface of the wide-bandgap perovskite film, modify the upper and lower interfaces of the perovskite layer, and adjust the interface energy levels for better matching, so as to prepare wide-bandgap perovskite cells with high open circuit voltage and high stability. Summary of the invention

[0005] In view of the problems of excessive open-circuit voltage loss and easy light-induced phase separation in wide-bandgap perovskite solar cells, the present invention discloses a method for preparing high-efficiency wide-bandgap perovskite cells using a new additive and a perovskite solar cell. By adding a certain amount of betaine citric acid to both the assembled monolayer (SAM) and the perovskite precursor solution for multifunctional passivation, a perovskite solar cell with higher open-circuit voltage, better photoelectric conversion efficiency and stability can be prepared.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:

[0007] A wide bandgap perovskite solar cell with high open circuit voltage, comprising a transparent conductive substrate, a hole transport layer, an organic-inorganic hybrid metal halide perovskite light absorption layer, a surface defect passivation layer, a metal fluoride layer, an electron transport layer, a hole blocking layer and a metal electrode;

[0008] The hole transport layer further comprises betaine citric acid, and the amount of betaine citric acid added is preferably 0.5 to 1% of the molar amount of the hole transport layer;

[0009] The organic-inorganic hybrid metal halide perovskite light absorbing layer further comprises citrate betaine, and preferably the added amount of the citrate betaine is 0.1 to 0.2% of the molar amount of the organic-inorganic hybrid metal halide perovskite light absorbing layer.

[0010] In some specific embodiments, the transparent conductive substrate is any one of etched ITO conductive glass and FTO conductive glass.

[0011] In some specific embodiments, the hole transport layer is nickel oxide (NiO X ) nanoparticles and self-assembled monolayers (SAMs).

[0012] In some specific embodiments, the organic-inorganic hybrid metal halide perovskite light absorbing layer Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W , wherein 0≤X≤0.05, 0.7≤Y≤0.85, 0≤Z≤0.05, 1.8≤W≤2.5; preferably, the thickness of the organic-inorganic hybrid metal halide perovskite light-absorbing layer is 300-800 nm.

[0013] In some specific embodiments, the surface defect passivation layer is a thin layer of a long-chain organic amine salt, preferably with a thickness of 50 to 100 nm.

[0014] In some specific embodiments, the metal fluoride layer is LiF, MgF 2 , NaF, preferably has a thickness of 0.8 to 1.2 nm.

[0015] In some specific embodiments, the electron transport layer is a fullerene derivative, preferably with a thickness of 25 to 30 nm.

[0016] In some specific embodiments, the hole blocking layer is bathocuproine (BCP), preferably with a thickness of 6 to 8 nm.

[0017] In some specific embodiments, the metal electrode is any one of Ag, Cu, and Au, and preferably has a thickness of 80 to 100 nm.

[0018] On the other hand, the method for preparing the aforementioned wide bandgap perovskite solar cell with high open circuit voltage comprises the following steps:

[0019] 1) Processing the transparent conductive substrate;

[0020] 2) Preparation of NiO XThe nanoparticle layer was prepared by dissolving the self-assembled monolayer (SAM) and betaine citrate powder in ethanol and using spin coating to prepare the hole transport layer;

[0021] 3) Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W The perovskite precursor powder and the citrate betaine powder are dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to prepare a perovskite precursor solution, and an organic-inorganic hybrid metal halide perovskite light absorbing layer is prepared by a spin coating method;

[0022] 4) preparing a surface defect passivation layer, a metal fluoride layer, an electron transport layer, a hole blocking layer and a metal electrode in sequence to obtain the wide bandgap perovskite solar cell with a high open circuit voltage.

[0023] In some specific embodiments, the self-assembled monolayer (SAM) in step 2) is Me-4PACz; preferably, the concentration of the Me-4PACz solution is 1-3 mmol / mL.

[0024] In some preferred embodiments, the film is formed by spin coating in step 2) at a rotation speed of 4000-5000 rpm for 30-40 seconds; the temperature during the spin coating process is 18-24° C.; and after the spin coating is completed, annealing is performed at 100-120° C. for 10-30 minutes.

[0025] In some specific embodiments, the Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W Perovskite precursor powders include CsI, FAI, RbI, MABr, PbI 2 and PbBr 2 ; The volume ratio of DMF and DMSO is (3.5-4.5):1, and the concentration of the perovskite precursor solution is 0.9-1.2 mmol / mL.

[0026] In some specific embodiments, the spin coating method of step 3) for preparing the organic-inorganic hybrid metal halide perovskite light absorbing layer further includes using chlorobenzene as an anti-solvent to assist film formation, using a two-stage spin coating method, the first stage has a rotation speed of 1000-2000 rpm, the time is 5-10s, the second stage has a rotation speed of 4000-5000 rpm, the time is 30-40s, and 100-150 μL of chlorobenzene is added dropwise at the last 15-20s of the second stage;

[0027] In some preferred embodiments, the temperature during the spin coating process is 18-24° C.; after the spin coating is completed, annealing is performed at 100-120° C. for 20-40 min.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The hole layer prepared by the present invention has better wettability. By adding betaine citrate to the self-assembled monolayer (SAM), the contact angle of the perovskite solution on the hole layer of the embodiment is significantly reduced, which is conducive to the growth of perovskite grains.

[0030] 2) The grain size of the perovskite film prepared by the present invention is significantly increased and the grain arrangement is denser; the defect density of the optimized perovskite film is significantly reduced compared with the untreated film.

[0031] 3) The perovskite solar cell prepared by the present invention has higher open circuit voltage and fill factor, and the photoelectric conversion efficiency is significantly improved. The present invention will effectively promote the commercialization process of perovskite solar energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Graph showing contact angles of the perovskite solution of the present invention in the cavity layer of Comparative Example 1 and Example 1.

[0033] Figure 2 These are SEM images of the perovskite film surfaces of Comparative Example 1 and Example 1 of the present invention.

[0034] Figure 3 SCLC diagram of the perovskite solar cell of Comparative Example 1 and Example 1 of the present invention.

[0035] Figure 4 It is a comparison diagram of the IV curves of the perovskite solar cells of Comparative Example 1 and Example 1 of the present invention.

[0036] Figure 5 It is a schematic diagram of the structure of a wide bandgap perovskite solar cell of the present invention. DETAILED DESCRIPTION

[0037] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0038] A wide bandgap perovskite solar cell with high open circuit voltage, as shown in the attached Figure 5 As shown, it consists of a transparent conductive substrate 1, a hole transport layer 2, an organic-inorganic hybrid metal halide perovskite light absorption layer 3, a surface defect passivation layer 4, a metal fluoride layer 5, an electron transport layer 6, a hole blocking layer 7 and a metal electrode 8.

[0039] In the present invention, the transparent conductive substrate 1 is any one of etched ITO conductive glass and FTO conductive glass. The transparent conductive substrate of the present invention is a common substrate in the art and can be etched and cleaned according to the prior art without any special limitation.

[0040] In the present invention, the hole transport layer 2 is nickel oxide (NiO X ) nanoparticles and self-assembled monolayers (SAM). Among them, nickel oxide (NiO X ) nanoparticles are usually 5 nm in size, and nickel oxide (NiO X ) layer has a thickness of 100 to 200 nm; the self-assembled monolayer (SAM) is preferably [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz). The hole transport layer of the present invention further comprises citrate betaine, which is preferably added together with the Me-4PACz, and the added amount is 0.5 to 1% of the molar amount of the hole transport layer (Me-4PACz), such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., preferably 0.5%.

[0041] In the present invention, the organic-inorganic hybrid metal halide perovskite light absorbing layer 3 is

[0042] Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W , wherein 0≤X≤0.05, 0.7≤Y≤0.85, 0≤Z≤0.05, 1.8≤W≤2.5; specifically, the organic-inorganic hybrid metal halide perovskite is Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3. Preferably, the thickness of the organic-inorganic hybrid metal halide perovskite light absorbing layer is 300-800nm, for example, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, but not limited thereto. The organic-inorganic hybrid metal halide perovskite light absorbing layer of the present invention also contains citrate betaine, and the amount of citrate betaine added is preferably 0.1-0.2% of the molar amount of the organic-inorganic hybrid metal halide perovskite light absorbing layer, for example, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, but not limited thereto. There is no particular restriction on the way of adding the citrate betaine, for example, adding it to

[0043] Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 Perovskite precursor powder is made into a perovskite precursor solution.

[0044] In the present invention, the surface defect passivation layer 4 is a long-chain organic amine salt thin layer, and the long-chain organic amine salt is, for example, an organic amine salt having 7 to 10 carbon atoms, preferably phenethyl ammonium bromide; the thickness of the long-chain organic amine salt thin layer is preferably 50 to 100 nm, for example, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc. Usually, the long-chain organic amine salt solution is spun dropwise onto the surface of the perovskite film, and annealed to form the surface defect passivation layer. There is no particular restriction on the concentration of the long-chain organic amine salt solution, for example, 0.5-1.0 mmol / mL, and after the spun dropwise formation of a thin layer, annealing is performed at 100°C for 5 minutes.

[0045] In the present invention, the metal fluoride layer 5 is LiF, MgF 2 , NaF, preferably has a thickness of 0.8 to 1.2 nm, such as 0.9 nm, 1 nm, and preferably 1 nm.

[0046] In the present invention, the electron transport layer 6 is a fullerene derivative, such as C60, and the thickness of the electron transport layer is preferably 25 to 30 nm, such as 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, etc., but not limited thereto.

[0047] In the present invention, the hole blocking layer 7 is bathocuproine (BCP), and preferably has a thickness of 0.8 to 1.2 nm, such as 0.9 nm, 1 nm, 1.1 nm, and preferably 1 nm.

[0048] In the present invention, the metal electrode 8 is any one of Ag, Cu and Au, and preferably has a thickness of 80 to 100 nm, such as 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc., but is not limited thereto.

[0049] In the present invention, the transparent conductive substrate 1, surface defect passivation layer 4, metal fluoride layer 5, electron transport layer 6, hole blocking layer 7 and metal electrode 8 may refer to the prior art unless otherwise specified, which is well known to those skilled in the art and will not be described in detail in the present invention.

[0050] On the other hand, the present invention also provides a method for preparing the above wide bandgap perovskite solar cell, comprising the following steps:

[0051] 1) Processing the transparent conductive substrate;

[0052] 2) Preparation of NiO X The nanoparticle layer was prepared by dissolving the self-assembled monolayer (SAM) and betaine citrate powder in ethanol and using spin coating to prepare the hole transport layer;

[0053] 3) Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W The perovskite precursor powder and the citrate betaine powder were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and the organic-inorganic hybrid metal halide perovskite light absorbing layer was prepared by spin coating;

[0054] 4) sequentially preparing a surface defect passivation layer, a metal fluoride layer, an electron transport layer, a hole blocking layer and a metal electrode to obtain the bandgap perovskite solar cell.

[0055] In the present invention, the self-assembled monolayer (SAM) in step 2) is Me-4PACz; preferably, the concentration of the Me-4PACz solution is 1-3 mmol / mL, for example, 1 mmol / mL, 1.2 mmol / mL, 1.3 mmol / mL, 1.5 mmol / mL, 1.8 mmol / mL, 2 mmol / mL, 2.3 mmol / mL, 2.5 mmol / mL, 2.8 mmol / mL, etc.

[0056] In the present invention, the amount of betaine citrate added to the hole transport layer of the present invention is 0.5-1% of the molar amount of the self-assembled monolayer (SAM), specifically, for example, 0.5-1% of the molar amount of Me-4PACz, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, but not limited thereto.

[0057] In the present invention, in step 2), the film is formed by spin coating, the rotation speed is 4000-5000rpm, for example, 4000rpm, 4200rpm, 4500rpm, 4800rpm, etc., the time is 30-40s, for example, 31s, 32s, 33s, 34s, 35s, 36s, 37s, 38s, 39s, etc.; the temperature of the spin coating process is 20-24°C, for example, 21°C, 22°C, 23°C, etc.; after the spin coating is completed, annealing is performed at 100°C for 10-20min, for example, 12min, 15min, 18min, 20min, etc.

[0058] In the present invention, the Cs in step 3) X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W Perovskite precursor powders include CsI, FAI, RbI, MABr, PbI 2 and PbBr 2 ; The volume ratio of DMF and DMSO is (3.5-4.5):1, for example, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, etc., and the concentration of the perovskite precursor solution is 0.9-1.2 mmol / mL, for example, 0.9 mmol / mL, 0.95 mmol / mL, 1.0 mmol / mL, 1.05 mmol / mL, 1.1 mmol / mL, 1.15 mmol / mL, 1.2 mmol / mL, etc.

[0059] In the present invention, the amount of betaine citrate added to the organic-inorganic hybrid metal halide perovskite light absorbing layer is 0.1 to 0.2% of the molar weight of the organic-inorganic hybrid metal halide perovskite light absorbing layer, for example, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, but not limited to this.

[0060] In the present invention, the spin coating method of step 3) for preparing the organic-inorganic hybrid metal halide perovskite light absorbing layer also includes using chlorobenzene as an anti-solvent to assist film formation, using a two-stage spin coating method, the first stage speed is 1000-2000rpm, such as 1200rpm, 1500rpm, 1800rpm, 2000rpm, etc., the time is 5-10s, such as 5s, 6s, 7s, 8s, 9s, etc.; the second stage speed is 4000- 5000rpm, for example, 4000rpm, 4200rpm, 4500rpm, 4800rpm, etc., for 30-40s, for example, 31s, 32s, 33s, 34s, 35s, 36s, 37s, 38s, 39s, etc., and 100-150μL of chlorobenzene, for example, 110μL, 120μL, 130μL, 140μL of chlorobenzene, is added dropwise at the last 15-20s of the second section.

[0061] In the present invention, in the spin coating method of step 3), the spin coating process temperature is 18-24°C, for example, 19°C, 20°C, 21°C, 22°C, 23°C, etc.; after the spin coating is completed, annealing is performed at 100-120°C for 20-40min, for example, annealing is performed at 110°C for 21min, 22min, 23min, 25min, 30min, 35min, etc.

[0062] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0063] The main raw materials used in the following examples are from the following sources:

[0064] NiO X Nanoparticles were purchased from Youxuan Technology Co., Ltd. [4-(3,6-dimethyl-9H-carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) powder, betaine citrate, phenethylammonium bromide, CsI, FAI, RbI, MABr, PbI 2 、PbBr 2 , LiF, C60 and BCP were purchased from Xi'an Biolight Company.

[0065] The main test methods involved in the following embodiments are as follows:

[0066] The single drop volume of the perovskite precursor was set to 2 μL, and the surface contact angle value was recorded 5 seconds after it was dropped onto the substrate. The morphology of the film was measured by SEM (JEOL, JSM-7500F, 104 Japan) at an accelerating voltage of 5.0 KV. In the spatial confinement current (SCLC) test, ITO / hole transport layer / perovskite light absorption layer / electron transport layer / Ag pure electronic structure devices were prepared to measure the current-voltage change curves of different devices in the dark state. The trap-filled limit voltage (V TFL ). The defect state density of the film is calculated according to the following formula:

[0067] n trap =2εε 0 V TFL / eL 2

[0068] Among them, ε, ε 0 and e represent the relative dielectric constant, vacuum dielectric constant and elementary charge of perovskite, respectively, and L represents the thickness of the perovskite layer.

[0069] The current density-voltage (IV) was measured in a glove box (N 2 The illumination current was measured under simulated sunlight (Lien Technology, 100 mW / cm 2 and AM 1.5G irradiation). The forward scan range is 0 to 1400mV, and the reverse scan range is 1400mV to 0mV, with a step size of 2.0mV.

[0070] Example 1

[0071] 1) The etched ITO conductive substrate was ultrasonically cleaned 3 times with deionized water, each cleaning time was 30 minutes;

[0072] 2) Treat the cleaned ITO conductive substrate with UVO for 20 min and spin-coat 12 mg / ml NiO X Nanoparticles in aqueous solution.

[0073] 3) Weigh [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) powder and betaine citrate powder, dissolve in ethanol, wherein the concentration of Me-4PACz solution is 0.5 mmol / mL, and the amount of betaine citrate added is 1 mol%. Spin-coat the Me-4PACz ethanol solution with betaine citrate added.

[0074] 4) Weigh Cs 0.05 MA0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 Perovskite precursor powder and betaine citrate were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the molar ratio of CsI to FAI was 1:17, the molar ratio of MABr to FAI was 1:17, and the molar ratio of PbI 2 and PbBr 2 The molar ratio of DMF to FAI is 20:17, the amount of betaine citrate added is 1.5 mol‰, the volume ratio of DMF to DMSO is 4:1, and the concentration of the perovskite precursor solution is 1.1 mmol / mL.

[0075] The obtained precursor solution was evenly spread on the ITO substrate treated with Me-4PACz + betaine citrate, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage rotation speed of 2000 rpm and a time of 10 s, and a second-stage rotation speed of 5000 rpm and a time of 40 s. 150 μL of chlorobenzene was added at the 15th second before the end of the second stage.

[0076] The obtained perovskite film was annealed at 100 °C for 30 min.

[0077] 5) Post-treatment of the annealed perovskite film: drop 1 mg / ml phenethylammonium bromide solution on the spin-coated perovskite film and anneal at 100° C. for 5 min.

[0078] 6) The obtained perovskite film was sequentially deposited with 1 nm of LiF, 25 nm of C60, 7 nm of BCP, and 100 nm of Ag.

[0079] Example 2

[0080] 1) The etched ITO conductive substrate was ultrasonically cleaned 3 times with deionized water, each cleaning time was 30 minutes;

[0081] 2) Treat the cleaned ITO conductive substrate with UVO for 20 min and spin-coat 12 mg / ml NiO X Nanoparticles in aqueous solution.

[0082] 3) Weigh [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) powder and betaine citrate powder, dissolve in ethanol, wherein the concentration of Me-4PACz solution is 0.5 mmol / mL, and the amount of betaine citrate added is 1 mol%. Spin-coat the Me-4PACz ethanol solution with betaine citrate added.

[0083] 4) Weigh Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 Perovskite precursor powder and betaine citrate were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the molar ratio of CsI to FAI was 1:17, the molar ratio of MABr to FAI was 1:17, and the molar ratio of PbI 2 and PbBr 2 The molar ratio of DMF to FAI is 20:17, the amount of betaine citrate added is 1 mol‰, the volume ratio of DMF to DMSO is 4:1, and the concentration of the perovskite precursor solution is 1.1 mmol / mL.

[0084] The obtained precursor solution was evenly spread on the ITO substrate treated with Me-4PACz + betaine citrate, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage rotation speed of 2000 rpm and a time of 10 s, and a second-stage rotation speed of 5000 rpm and a time of 40 s. 150 μL of chlorobenzene was added at the 15th second before the end of the second stage.

[0085] The obtained perovskite film was annealed at 100 °C for 30 min.

[0086] 5) Post-treatment of the annealed perovskite film: drop 1 mg / ml phenethylammonium bromide solution on the spin-coated perovskite film and anneal at 100° C. for 5 min.

[0087] 6) The obtained perovskite film was sequentially deposited with 1 nm of LiF, 25 nm of C60, 7 nm of BCP, and 100 nm of Ag.

[0088] Example 3

[0089] 1) The etched ITO conductive substrate was ultrasonically cleaned 3 times with deionized water, each cleaning time was 30 minutes;

[0090] 2) Treat the cleaned ITO conductive substrate with UVO for 20 min and spin-coat 12 mg / ml NiO X Nanoparticles in aqueous solution.

[0091] 3) Weigh [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) powder and betaine citrate powder, dissolve in ethanol, wherein the concentration of Me-4PACz solution is 0.5 mmol / mL, and the amount of betaine citrate added is 1 mol%. Spin-coat the Me-4PACz ethanol solution with betaine citrate added.

[0092] 4) Weigh Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 Perovskite precursor powder and betaine citrate were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the molar ratio of CsI to FAI was 1:17, the molar ratio of MABr to FAI was 1:17, and the molar ratio of PbI 2 and PbBr 2 The molar ratio of DMF to FAI is 20:17, the amount of betaine citrate added is 1 mol‰, the volume ratio of DMF to DMSO is 4:1, and the concentration of the perovskite precursor solution is 1.0 mmol / mL.

[0093] The obtained precursor solution was evenly spread on the ITO substrate treated with Me-4PACz + betaine citrate, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage rotation speed of 2000 rpm and a time of 10 s, and a second-stage rotation speed of 5000 rpm and a time of 40 s. 150 μL of chlorobenzene was added at the 15th second before the end of the second stage.

[0094] The obtained perovskite film was annealed at 100 °C for 30 min.

[0095] 5) Post-treatment of the annealed perovskite film: drop 1 mg / ml phenethylammonium bromide solution on the spin-coated perovskite film and anneal at 100° C. for 5 min.

[0096] 6) The obtained perovskite film was sequentially deposited with 1 nm of LiF, 25 nm of C60, 7 nm of BCP, and 100 nm of Ag.

[0097] Comparative Example 1

[0098] 1) The etched ITO conductive substrate was ultrasonically cleaned 3 times with deionized water, each cleaning time was 30 minutes;

[0099] 2) Treat the cleaned ITO conductive substrate with UVO for 20 min and spin-coat 12 mg / ml NiO XNanoparticles in aqueous solution.

[0100] 3) Weigh [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) powder and dissolve it in ethanol, wherein the concentration of Me-4PACz solution is 0.5 mmol / mL. Spin-coat 0.5 mmol / mL Me-4PACz ethanol solution.

[0101] 4) Weigh Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 The perovskite precursor powder was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), in which the molar ratio of CsI to FAI was 1:17, the molar ratio of MABr to FAI was 1:17, and the molar ratio of PbI 2 and PbBr 2 The molar ratio of DMF to FAI is 20:17. The volume ratio of DMF to DMSO is 4:1, and the concentration of the perovskite precursor solution is 1.1 mmol / mL.

[0102] The obtained precursor solution was evenly spread on the ITO substrate treated with Me-4PACz, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage rotation speed of 2000 rpm and a time of 10 s, and a second-stage rotation speed of 5000 rpm and a time of 40 s. 150 μL of chlorobenzene was added at the 15th second before the end of the second stage.

[0103] The obtained perovskite film was annealed at 100 °C for 30 min.

[0104] 5) Post-treatment of the annealed perovskite film: Spin-drop 1.5 mg / ml phenethylammonium bromide solution on the spin-coated perovskite film and anneal at 100° C. for 5 min.

[0105] 6) The obtained perovskite film was sequentially deposited with 1 nm of LiF, 25 nm of C60, 7 nm of BCP, and 100 nm of Ag.

[0106] Comparative Example 2

[0107] 1) The etched ITO conductive substrate was ultrasonically cleaned 3 times with deionized water, each cleaning time was 30 minutes;

[0108] 2) Treat the cleaned ITO conductive substrate with UVO for 20 min and spin-coat 12 mg / ml NiO X Nanoparticles in aqueous solution.

[0109] 3) Weigh [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) powder and betaine citrate powder, dissolve in ethanol, wherein the concentration of Me-4PACz solution is 0.5 mmol / mL, and the amount of betaine citrate added is 1 mol%. Spin-coat the Me-4PACz ethanol solution with betaine citrate added.

[0110] 4) Weigh Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 The perovskite precursor powder was dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), in which the molar ratio of CsI to FAI was 1:17, the molar ratio of MABr to FAI was 1:17, and the molar ratio of PbI 2 and PbBr 2 The molar ratio of DMF to FAI is 20:17. The volume ratio of DMF to DMSO is 4:1, and the concentration of the perovskite precursor solution is 1.1 mmol / mL.

[0111] The obtained precursor solution was evenly spread on the ITO substrate treated with Me-4PACz, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage rotation speed of 2000 rpm and a time of 10 s, and a second-stage rotation speed of 5000 rpm and a time of 40 s. 150 μL of chlorobenzene was added at the 15th second before the end of the second stage.

[0112] The obtained perovskite film was annealed at 100 °C for 30 min.

[0113] 5) Post-treatment of the annealed perovskite film: Spin-drop 1.5 mg / ml phenethylammonium bromide solution on the spin-coated perovskite film and anneal at 100° C. for 5 min.

[0114] 6) The obtained perovskite film was sequentially deposited with 1 nm of LiF, 25 nm of C60, 7 nm of BCP, and 100 nm of Ag.

[0115] Comparative Example 3

[0116] 1) The etched ITO conductive substrate was ultrasonically cleaned 3 times with deionized water, each cleaning time was 30 minutes;

[0117] 2) Treat the cleaned ITO conductive substrate with UVO for 20 min and spin-coat 12 mg / ml NiO X Nanoparticles in aqueous solution.

[0118] 3) Weigh [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) powder and dissolve it in ethanol, wherein the concentration of Me-4PACz solution is 0.5 mmol / mL. Spin-coat 0.5 mmol / mL Me-4PACz ethanol solution.

[0119] 4) Weigh Cs 0.05 MA 0.05 R 0.05 FA 0.85 Pb(I 0.65 Br 0.35 ) 3 Perovskite precursor powder and betaine citrate were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), where the molar ratio of CsI to FAI was 1:17, the molar ratio of MABr to FAI was 1:17, and the molar ratio of PbI 2 and PbBr 2 The molar ratio of DMF to FAI is 20:17, the amount of betaine citrate added is 1.5 mol‰, the volume ratio of DMF to DMSO is 4:1, and the concentration of the perovskite precursor solution is 1.1 mmol / mL.

[0120] The obtained precursor solution was evenly spread on the ITO substrate treated with Me-4PACz + betaine citrate, and chlorobenzene was used as an anti-solvent to assist film formation. A two-stage spin coating method was used, with a first-stage rotation speed of 2000 rpm and a time of 10 s, and a second-stage rotation speed of 5000 rpm and a time of 40 s. 150 μL of chlorobenzene was added at the 15th second before the end of the second stage.

[0121] The obtained perovskite film was annealed at 100 °C for 30 min.

[0122] 5) Post-treatment of the annealed perovskite film: Spin-drop 1.5 mg / ml phenethylammonium bromide solution on the spin-coated perovskite film and anneal at 100° C. for 5 min.

[0123] 6) The obtained perovskite film was sequentially deposited with 1 nm of LiF, 25 nm of C60, 7 nm of BCP, and 100 nm of Ag.

[0124] Table 1 shows the relevant performance test parameters of the perovskite solar cell devices of the above embodiments and comparative examples.

[0125] Table 1

[0126]

[0127] The contact angles of the perovskite solution in the hole layer of Comparative Example 1 and Example 1 are shown in the attached figure. Figure 1As shown, the contact angle of the perovskite solution on the hole layer treated with citrate betaine is significantly reduced, indicating that the wettability of the hole layer with the addition of citrate betaine is better, which is conducive to the adhesion of the perovskite solution and further conducive to the growth of perovskite grains.

[0128] The SEM images of the perovskite films of Comparative Example 1 and Example 1 are shown in the attached Figure 2 As shown, the grain size of the perovskite light absorbing layer in Example 1 is significantly increased, and the grains are arranged more closely, which effectively reduces the holes inside the light absorbing layer and improves the quality of the film.

[0129] The SCLC curves of the perovskite solar cells of Comparative Example 1 and Example 1 are shown in the attached Figure 3 As shown, the trap filling limiting voltage of the perovskite solar cell in Example 1 is reduced, and the internal defects of the film are significantly reduced.

[0130] The IV curves of the perovskite solar cells of Comparative Example 1 and Example 1 are shown in the attached Figure 4 As shown, the open circuit voltage, short circuit current and fill factor of the perovskite solar cell in Example 1 are significantly increased, and ultimately a higher photoelectric conversion efficiency is achieved.

[0131] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A wide bandgap perovskite solar cell with high open circuit voltage, characterized in that: It consists of a transparent conductive substrate, a hole transport layer, an organic-inorganic hybrid metal halide perovskite light absorption layer, a surface defect passivation layer, a metal fluoride layer, an electron transport layer, a hole blocking layer and a metal electrode; The hole transport layer further comprises betaine citric acid, and the amount of betaine citric acid added is preferably 0.5 to 1% of the molar amount of the hole transport layer; The organic-inorganic hybrid metal halide perovskite light absorbing layer further comprises citrate betaine, and preferably the added amount of the citrate betaine is 0.1 to 0.2% of the molar amount of the organic-inorganic hybrid metal halide perovskite light absorbing layer.

2. The wide bandgap perovskite solar cell according to claim 1, characterized in that The transparent conductive substrate is any one of etched ITO conductive glass or FTO conductive glass; The hole transport layer is nickel oxide (NiO X ) nanoparticles and self-assembled monolayers (SAMs).

3. The wide bandgap perovskite solar cell according to claim 1, characterized in that: The organic-inorganic hybrid metal halide perovskite light absorbing layer is Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W , wherein 0≤X≤0.05, 0.7≤Y≤0.85, 0≤Z≤0.05, 1.8≤W≤2.5; preferably, the thickness of the organic-inorganic hybrid metal halide perovskite light-absorbing layer is 300-800 nm.

4. The wide bandgap perovskite solar cell according to claim 1, characterized in that: The surface defect passivation layer is a thin layer of long-chain organic amine salt, and preferably has a thickness of 50 to 100 nm.

5. The wide bandgap perovskite solar cell according to claim 1, characterized in that The metal fluoride layer is any one of LiF, MgF2, and NaF, and preferably has a thickness of 0.8 to 1.2 nm; the electron transport layer is a fullerene derivative, and preferably has a thickness of 25 to 30 nm.

6. The wide bandgap perovskite solar cell according to claim 1, characterized in that: The hole blocking layer is bathocuproin, preferably with a thickness of 6 to 8 nm; the metal electrode is any one of Ag, Cu, and Au, preferably with a thickness of 80 to 100 nm.

7. The method for preparing a wide bandgap perovskite solar cell with high open circuit voltage according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Processing the transparent conductive substrate; 2) Preparation of NiO X The nanoparticle layer was prepared by dissolving the self-assembled monolayer (SAM) and betaine citrate powder in ethanol and using spin coating to prepare the hole transport layer; 3) Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W The perovskite precursor powder and the citrate betaine powder are dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to prepare a perovskite precursor solution, and an organic-inorganic hybrid metal halide perovskite light absorbing layer is prepared by a spin coating method; 4) preparing a surface defect passivation layer, a metal fluoride layer, an electron transport layer, a hole blocking layer and a metal electrode in sequence to obtain the wide bandgap perovskite solar cell with a high open circuit voltage.

8. The preparation method according to claim 7, characterized in that: In step 2), the self-assembled monolayer (SAM) is Me-4PACz; preferably, the concentration of the Me-4PACz solution is 1-3 mmol / mL; Preferably, the film is formed by spin coating, with a rotation speed of 4000-5000 rpm and a time of 30-40 s; the temperature during the spin coating process is 18-24° C.; and after the spin coating is completed, annealing is performed at 100-120° C. for 10-30 min.

9. The preparation method according to claim 7, characterized in that: Step 3) Cs X FA Y MA Z R 1-X-Y-Z PbI W Br 3-W Perovskite precursor powders include CsI, FAI, RbI, MABr, PbI2, and PbBr2; Preferably, the volume ratio of DMF to DMSO is (3.5-4.5):1, and the concentration of the perovskite precursor solution is 0.9-1.2 mmol / mL.

10. The preparation method according to claim 7, characterized in that: Step 3) of the spin coating method for preparing the organic-inorganic hybrid metal halide perovskite light absorbing layer further includes using chlorobenzene as an anti-solvent to assist film formation, using a two-stage spin coating method, the first stage speed is 1000-2000 rpm, the time is 5-10s, the second stage speed is 4000-5000 rpm, the time is 30-40s, and 100-150 μL of chlorobenzene is added dropwise at the last 15-20s of the second stage; Preferably, the temperature during the spin coating process is 18-24° C.; after the spin coating is completed, annealing is performed at 100-120° C. for 20-40 min.